Trends in Nutritional Biomarkers by Demographic Characteristics Across 14 Years Among US Adults - Wang, Wenjie; Zhu, Fangzhou; Wu, Lanlan; Han, Shan; Wu, Xiaoyan (Frontiers in Nutrition, 2022)
Abstract: Background: Understanding trend in nutritional status is crucial to inform national health priorities to improve diets and reduce related diseases. The present study aimed to analyze trends in the concentrations of all measured nutritional biomarkers and their status among US adults across 14 years. Methods: Trends on the concentrations of nutritional biomarkers and nutritional status evaluated by the prevalence of deficiency, inadequacy, excess and dyslipidemia were analyzed among US adults in 7 cross-sectional National Health and Nutrition Examination Surveys (NHANES 2003-2016) and by age, sex, race/ethnicity and socioeconomic status. Results: A total of 38,505 participants (weighted mean age of 47.2 years, 51.4% female) were included in the present study. Across 14 years, increased trends were found in RBC folate, serum vitamin B12, vitamin D and albumin, the prevalence of iodine deficiency, vitamin B6 inadequacy and hypophosphatemia, whereas decreased trends were observed in serum vitamin E, phosphorus, total calcium, total protein, apolipoprotein B (Apo B), low-density-lipoprotein cholesterol (LDL-C), triglyceride (TG), total cholesterol (TC), blood lead, cadmium, mercury, and the prevalence of vitamin C deficiency, vitamin D inadequacy, iodine excess, and dyslipidemia with elevated LDL-C, TC, TG and lowered HDL/LDL. Non-Hispanic blacks and participants with low socioeconomic status accounted for the poor nutritional status of most biomarkers compared to their comparts. Conclusion: Most nutritional biomarkers and their status were improved among US adults from 2003 to 2016, but some specific populations should be paid much attention to improve their nutritional status, especially for non-Hispanic blacks and participants with low socioeconomic status.